The experiences of early career teachers: new initiatives and old problems. Issue 2 (15th March 2018) - Schuck, Sandy; Aubusson, Peter; Buchanan, John; Varadharajan, Meera; Burke, Paul F.
Abstract: The task of supporting beginning teachers has received considerable attention in recent years, and numerous initiatives have been implemented. In this article we investigate the experiences of early career teachers (ECTs) in New South Wales, Australia, at a time when their employing authority mandated the provision of mentors and a reduction in face-to-face teaching for ECTs. The article draws on ECTs' responses to survey items asking about their experiences as an ECT. It emerged that many of the issues of the early years that have caused problems for ECTs remain intractable, or at least unresolved for some. The research indicates that despite support that has been mandated by some employers, we cannot be complacent about the transition of ECTs into the profession. There remains a need to address the elements of school environments that impact on ECTs' experiences.